AN ANALYTICAL STUDY OF THE DANCE COMPOSITIONS OF KATHAK GURU DR. SUCHITRA HARMALKAR IN THE CONTEXT OF TRADITION AND SOCIAL AWARENESS - Mandlik, Yogita (International Journal of Research -GRANTHAALAYAH, 2026)
The fundamental objective of Indian classical arts has always been rooted in the philosophical ideal of “Satyam Shivam Sundaram” (Truth, Auspiciousness, Beauty). Since ancient times, dance has not only been a medium of devotion to deities but also a means of guiding society toward moral values. In the present context, when society faces multiple challenges and contradictions, the role of art has become even more significant. Renowned Kathak exponent Dr. Suchitra Harmalkar of the Raigarh gharana has preserved the purity of Kathak while establishing it as a platform for social discourse. Classical dance is often perceived as being confined to mythological narratives; however, Dr. Harmalkar has challenged this notion by connecting the traditional vocabulary of Kathak with contemporary social issues. Her choreographed dance-dramas are not merely stage performances but reflections of an artist’s sensitivity toward society. This research analyzes her major choreographic works based on themes such as environmental conservation and women’s empowerment. It highlights how, through expressive gestures and rhythmic structures, she has effectively communicated complex social messages to the public in an accessible and impactful manner. The study employs both primary and secondary sources, including video recordings of performances, reviews, and interviews reflecting her artistic vision.